Accurate and Robust Spectral Testing with Relaxed Instrumentation Requirements - Zhuang, Yuming (Springer International Publishing, 2018)
This book introduces a family of new methods for accurate and robust spectral testing and fills an information gap, as the requirements in standard test have grown increasingly challenging in recent high precision testing, especially as the device performance has continued to improve. Test engineers will be enabled to accurately set their devices & systems at much simpler test setup, much reduced complexity and much lower cost.